STUDY OF WEAR BEHAVIOUR OF Al/ (Al2O3P and SiCP) HYBRID METAL MATRIX COMPOSITES - Radhika, N.; Praveen, G.; Rathan, P Gautham (Malaysian Journal of Science, 2014)
In this study, dry sliding wear behaviour of Aluminium Hybrid Metal Matrix Composite was investigated and a prediction model was developed using Taguchi’s method. Aluminium A356alloy reinforced with equal weight percentage of alumina and silicon carbide particles (10wt%, 20wt% and 30wt %) was produced using liquid metallurgy method. Experiments were conducted using Pin-on-disc tester. The sliding distance was kept constant and the effect of load, sliding velocity and weight percentage of reinforcement on the wear properties was evaluated. It was found that as load increases, wear rate also increases and it decreases as sliding velocity increases. By increasing weight percentage of reinforcements, the wear resistance increases and was found that 30% reinforced composite had less wear rate. The prediction model showed that the major parameter that influences the wear rate was load followed by weight percentage of reinforcement and sliding velocity. By confirmation test, the predicted wear rates were found to be close to the experimental values. Based on this approach, it was found that the improvement in the wear resistance of hybrid composites became more significant at high sliding velocity, low load and with high weight percentage of reinforcements. Keywords: Dry sliding wear, Metal Matrix Composite, Alumina, Silicon carbide, Prediction model, Taguchi’s method